Oracle enterprise manager 12c command-line interface - Pot'Vin, Kellyn (Apress, 2014)
Oracle Enterprise Manager 12c Command-Line Interface shows how to use Enterprise Manager's powerful scripting language to automate your database administration work and save time by scripting routine tasks, and then executing those scripts across collections of databases and instances in your environment. This book is chock full of ready-made scripting examples contributed by the authors and leading members of the community. For example, you'll find scripts and examples of commands to: Remove an Enterprise Manager agent and its related targets Quickly create administrator accounts that are fully-configured with pre-expired passwords and all needed roles Invoke batch files to execute sequences of related commands with consistency against multiple targets Batch create large groups of user logins with a single command and more! The Enterprise Manager Command Line Interface (EM CLI) is the administrator's key to unlocking the power of Enterprise Manager 12c (EM12c) with scalability, repeatability, and confidence. In previous versions, most administrators ventured into the command-line interface only with the assistance of Oracle Support. But now there are many features in EM12c that are accessible only from the command-line. This is far from a disadvantage! Enterprise Manager is now a powerful tool for automation in the hands of a skilled database administrator. Enterprise Manager scripting offers potential for all administrators who manage Oracle's enterprise-level products in their environment. You can automate from the smallest, single-instance configuration all the way up to a broadly distributed enterprise-level rollout having database instances strewn across broad geographical distributions. The power of the EM CLI returns the administrator to the golden age, where the entire environment, from database to application to infrastructure, can often be managed from this powerful command line tool secured by the robust Enterprise Manager framework. Brings a golden-age of automation to Oracle Database administrators Provides ready-made scripts contributed by leading members of the community Covers advanced techniques involving Jython and Python